The influence of melt status and beta-nucleation agent distribution on the crystallization of isotactic polypropylene. Issue 13 (8th March 2022) - Chen, Pujing; Xu, Min; Li, Xiangyang; Han, Yu; Ding, Jianjun; Lin, Yongxing; Liu, Gang; Zhang, Xian; Chen, Lin; Tian, Xingyou
Abstract : Although investigated extensively in past decades, the factors affecting β-crystallization in β-nucleating agent/iPP composites have not been identified completely. Abstract : Although investigated extensively in past decades, the factors affecting β-crystallization in β-nucleating agent/iPP composites have not been identified completely. In this study, β-crystallization in mesomorphic melt and free melt with 0.05 wt% WBG-II was investigated at various melting and crystallization temperatures, employing polarized optical microscopy, scanning electron microscopy, differential scanning calorimetry, and synchrotron small-angle and wide-angle X-ray diffraction. It was found that β-nucleation efficiency and thermodynamic stability of β-crystals depended strongly on the melting temperature. Higher β-nucleation efficiency and thermodynamic stability can be obtained only when the melting temperature was below 195 °C, where the β-nucleating agent (β-NA) was well dispersed in the melt. Further, ordered structures in the mesomorphic structured melt can further promote the formation of more perfect β-crystals. It is thought that β-NA distribution and ordered structures in the polymer melt are the two key factors affecting the formation of β-crystals. The former affects the number of β-nucleating sites accessible for iPP chains, while the latter affects the growth of β-crystals. Only when β-NA is well dispersed and the iPP melt exists massive chiral intrachain clusters similar to β-crystals, can perfect β-crystals be induced fully.